2014
DOI: 10.1002/jobm.201300867
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of soil diazotrophic community structure, diversity, and functioning during the cropping period of cotton (Gossypium hirsutum)

Abstract: The soil sampled at different growth stages along the cropping period of cotton were analyzed using various molecular tools: restriction fragment length polymorphism (RFLP), terminal restriction length polymorphism (T-RFLP), and cloning-sequencing. The cluster analysis of the diazotrophic community structure of early sampled soil (0, 15, and 30 days) was found to be more closely related to each other than the later sampled one. Phylogenetic and diversity analysis of sequences obtained from the first (0 Day; C0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…cotton seeds with 79.50 % and was fifth rank followed by non-availability of information about future aberrant weather conditions with 78.00 % and was six rank followed by lack of co-ordination between farmer and agriculture institution with 76.50 % and was seven rank followed by scarcity of labour at plucking stage with 73.50 % and was eight rank followed by reduction in the yield of cotton due to insects with 71.00 % and was nine rank followed by lack of technical knowledge about the recommended insecticide, pesticide, fungicide and herbicide with 68.00 % and was ten rank followed by high price of fertilizers with 65.50 % and was eleven rank followed by irregular supply of electricity with 65.00 % and was twelve rank followed by lack of knowledge to diagnose the pests , diseases and weeds in the crop with 63.50 % and was thirteen rank. Similar findings were reported by Raghavendra [5], Rai et al [6], Mahendrakar et al [7], Goud et al [8], Kumar et al [9], Sardhara et al [10], Ahmad et al [11] and Shwetha et al [12].…”
Section: Constraints Experienced By the Cotton Growers In Adoption Of...supporting
confidence: 88%
“…cotton seeds with 79.50 % and was fifth rank followed by non-availability of information about future aberrant weather conditions with 78.00 % and was six rank followed by lack of co-ordination between farmer and agriculture institution with 76.50 % and was seven rank followed by scarcity of labour at plucking stage with 73.50 % and was eight rank followed by reduction in the yield of cotton due to insects with 71.00 % and was nine rank followed by lack of technical knowledge about the recommended insecticide, pesticide, fungicide and herbicide with 68.00 % and was ten rank followed by high price of fertilizers with 65.50 % and was eleven rank followed by irregular supply of electricity with 65.00 % and was twelve rank followed by lack of knowledge to diagnose the pests , diseases and weeds in the crop with 63.50 % and was thirteen rank. Similar findings were reported by Raghavendra [5], Rai et al [6], Mahendrakar et al [7], Goud et al [8], Kumar et al [9], Sardhara et al [10], Ahmad et al [11] and Shwetha et al [12].…”
Section: Constraints Experienced By the Cotton Growers In Adoption Of...supporting
confidence: 88%
“…Two independent studies on the microbial community in the root of the model plant Arabidopsis thaliana revealed consistent results on the core microbiome, with Actinobacteria and a few families from Proteobacteria enriched consistently in the endosphere compared with rhizosphere 11,12 . Microbiomes from various tissues of many crops such as sugarcane, rice, tomato, maize, sorghum, soybean, and cotton have been characterized to various degrees [13][14][15][16][17][18][19] . Microbiomes from certain tissues of fruits and trees including pear, banana, and apple have initially analyzed as well [20][21][22] .…”
mentioning
confidence: 99%
“…However, molecular study clearly demonstrated variation in bacterial diversity under different cropping systems, which was not reflected in the metabolic profiles of bacteria of soils. Rai et al (2010) observed that there was no correlation between microbial diversity and microbial activity. Nannipieri et al (2003) stated that no relation exists between microbial diversity and decomposition of organic matter, and a reduction in any group of species has little effect on overall soil process because the surviving microorganisms can carry out the decomposition of organic matter.…”
Section: Discussionmentioning
confidence: 95%
“…Microbial community profiles of continuous cultivation soils were different from profiles of rotation soils. Rai et al (2010) studied the dynamics of soil microbial community structure by ARDRA and activity during the cropping period of cotton. These authors did not find any correlation between the microbial activity and community structure.…”
Section: Introductionmentioning
confidence: 99%